Generation, Annotation, and Analysis of a Large-Scale Expressed Sequence Tag Library from Arabidopsis pumila to Explore Salt-Responsive Genes - Huang, Xianzhong; Yang, Lifei; Jin, Yuhuan; Lin, Jun; Liu, Fang (Frontiers in Plant Science, 2017)
Arabidopsis pumila is an ephemeral plant, and a close relative of the model plant Arabidopsis thaliana, but it possesses higher photosynthetic efficiency, higher propagation rate, and higher salinity tolerance compared to those A. thaliana, thus providing a candidate plant system for gene mining for environmental adaption and salt tolerance. However, A. pumila is an under-explored resource for understanding the genetic mechanisms underlying abiotic stress adaptation. To improve our understanding of the molecular and genetic mechanisms of salt stress adaptation, more than 19,900 clones randomly selected from a cDNA library constructed previously from leaf tissue exposed to high-salinity shock were sequenced. A total of 16,014 high-quality expressed sequence tags (ESTs) were generated, which have been deposited in the dbEST GenBank under accession numbers JZ932319 to JZ948332. Clustering and assembly of these ESTs resulted in the identification of 8,835 unique sequences, consisting of 2,469 contigs and 6,366 singletons. The blastx results revealed 8,011 unigenes with significant similarity to known genes, while only 425 unigenes remained uncharacterized. Functional classification demonstrated an abundance of unigenes involved in binding, catalytic, structural or transporter activities, and in pathways of energy, carbohydrate, amino acid, or lipid metabolism. At least seven main classes of genes were related to salt-tolerance among the 8,835 unigenes. Many previously reported salt tolerance genes were also manifested in this library, for example VP1, H+-ATPase, NHX1, SOS2, SOS3, NAC, MYB, ERF, LEA, P5CS1. In addition, 251 transcription factors were identified from the library, classified into 42 families. Lastly, changes in expression of the 12 most abundant unigenes, 12 transcription factor genes, and 19 stress-related genes in the first 24 h of exposure to high-salinity stress conditions were monitored by qRT-PCR. The large-scale EST library obtained in this study provides first-hand information on gene sequences expressed in young leaves of A. pumila exposed to salt shock. The rapid discovery of known or unknown genes related to salinity stress response in A. pumila will facilitate the understanding of complex adaptive mechanisms for ephemerals.